THE ROLE OF RELIGIOUS FIGURES IN COMMUNITY RESILIENCE IN DISASTER-PRONE AREAS - Muhasim Muhasim; Zulfikar Muhammad; Janes Jainurakhma (Lisan Al-Hal: Jurnal Pengembangan Pemikiran dan Kebudayaan)
Religious leaders in Indonesia are one of the keys to the success of community resilience to disasters, especially in socializing and communicating disaster resilience and giving early warnings appropriately and accurately to the community. The purpose of this study is to explore the role of religious figures in disaster resilience among Muslim communities affected by the eruption of Mount Kelud. This research uses a qualitative approach using interpretive phenomenological methods. Purposive sampling is the way used in this study, with criteria: religious and community leaders who live in Pandan Sari Village, Ngantang District, Malang Regency, have experienced or been affected by the eruption of Mount Kelud, and are not deaf. Semi-structured interviewing methods were used, and Colaizzi's model approach was used for analysis. The results of the study found that there were five themes, including (1) being active in disaster management planning activities; (2) being active in the involvement of cooperation and protection of Muslim communities in the village; (3) playing an active role as a disaster volunteer; (4) play an active role as a presenter of information against early warning; (5) play an active role in physical mitigation. The recommendation that can be given is the need for religious figures to be involved in every disaster mitigation activity in the village area because the role of religious figures greatly affects the resilience of community disasters in the village area.